2018
DOI: 10.14716/ijtech.v9i5.1467
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Optimisation of Biogas Potential in Co-Digestion of Miscanthus Fuscus and Cow Dung

Abstract: In this study, the effects of co-digestion operating conditions for the enhancement of biogas production from Miscanthus Fuscus mixed with cow dung, was investigated. The aforementioned organic wastes are good substrate resources for anaerobic co-digestion (AD) due to their high content of easily biodegradable materials. This source of effective and ecofriendly technology as AD is for generating energy from organic waste. Response surface methodology (RSM) based on the Box-Behnken (BBD) design was employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 21 publications
1
23
1
Order By: Relevance
“…In the mathematical model (Equation 6), Y represents the response xiu while xju are the input parameters (factors), b0 is the constant of the regression equation, bi are the linear coefficients, bii are the quadratic coefficients, bij are the interaction coefficients, and ɛ is the fitting error Wang et al, 2007;Tetteh et al, 2018).…”
Section: Development Of Mathematical Modelmentioning
confidence: 99%
“…In the mathematical model (Equation 6), Y represents the response xiu while xju are the input parameters (factors), b0 is the constant of the regression equation, bi are the linear coefficients, bii are the quadratic coefficients, bij are the interaction coefficients, and ɛ is the fitting error Wang et al, 2007;Tetteh et al, 2018).…”
Section: Development Of Mathematical Modelmentioning
confidence: 99%
“…the response surface methodology (RSM). The response surface methodology is a systematic methodology that consists of a group of mathematical and statistical techniques for experimental design, independent and interdependent analysis, model development and exploitation [37,38]. The empirical model (Equation (1)) is a relationship between process variables and the expected response to understand the process mechanism and to optimize the process using minimal experimental runs [39].…”
Section: Introductionmentioning
confidence: 99%
“…This anaerobic digestion process produced a biogas volume of approximately 28 m 3 with a high CO2 content per ton of POME (Harsono et al, 2014). Tetteh et al (2018) reported using an organic waste source such as cow dung for biogas production. It promotes waste generation and has promising implications for green energy for use in improved economic and environmental applications (Tetteh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tetteh et al (2018) reported using an organic waste source such as cow dung for biogas production. It promotes waste generation and has promising implications for green energy for use in improved economic and environmental applications (Tetteh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%